Simplified fluctuation test to distinguish liquid holding recovery from cell multiplication in ultraviolet-irradiated Escherichia coli. - Aragão, B R (1980)
Improved plating techniques and a fluctuation test have been used to distinguish between liquid holding recovery of ultraviolet-irradiated cells and cell multiplication in Escherichia coli. Among tested strains, only recA mutants showed true recovery.